Exploring Elementary School Teachers’ Views About Gamification as Learning Media in Their Science Classroom - Rindu Rahmatiah; Joni Rokhmat; A. Wahab Jufri; Gunawan Gunawan; A A Sukarso (Indonesian Journal of Teacher Education, 2023)
Gamification is a relatively new concept in education that is often discussed in current research. This research aims to understand elementary science teachers' perspectives on gamification as a learning medium in their science classrooms. This research is survey research. There are 18 open questions in the questionnaire, which was distributed via Google Forms and voluntarily completed by 70 science teachers from elementary schools in Mataram, Indonesia. The teacher respondents in this research have 1 to 40 years of experience teaching science. The results show that almost 70% of teacher respondents are unfamiliar with and have never used gamification in their science classes. Even among those already familiar with gamification, very few understand its elements and how to apply them effectively. These results showed that gamification is a relatively new concept for the teacher respondents in this survey. It also illustrates that introducing gamification to them is appropriate.